Congenital Internal Hydrocephalus in a Swine - Neves, Marina Resgala; de Paula Júnior, Gil Fernando; Conceição, Fábia Fernanda Cardoso de Barros; Varaschin, Mary Suzan; Lacreta Júnior, Antônio Carlos Cunha; Sousa, Ticiana Meireles; Coutinho, Adriana de Souza; Toma, Hugo Shisei (Acta Scientiae Veterinariae, 2025)
Background: An active distension of the brain's ventricular system related to the inadequate passage of cerebrospinal fluid (CSF) characterizes hydrocephalus, with usually occurs due to an interruption in the flow or absorption of CSF. Congenital hydrocephalus occurs in several animal species, being rare in pigs. Farm animals generally show clinical signs at birth, while pet animals after a few months. The imaging tests normally used are ultrasound, magnetic resonance imaging, and computed tomography. This report aims to describe the clinical, radiographic, ultrasound and pathological features of 1 case of congenital hydrocephalus in a pig. Case: A case of congenital internal hydrocephalus in a male pig, 8-hour-old, weighing 1,800 kg, presented in the physical examination, an enlarged skull, motor incoordination and permanent lateral decubitus. On physical examination, the physiological parameters were within normal limits, however, he was in lateral decubitus, unable to maintain himself in sternal decubitus or station, and did not present a sucking reflex. In the neurological examination, it was observed that the animal was alert, but had muscle tremors and ataxia of all four limbs. Imaging exams were also performed, on simple radiographic examination an increase in volume of the cranial vault is noted, with a homogeneous appearance of the brain, with predominantly liquid/soft tissue radiopacity, with the absence of markings of the cerebral convolutions and bone cortical thinning in the calvaria region. The radiographic findings of the contrast examination (myelography) did not demonstrate progression of the contrast medium into the subarachnoid space of the spinal cord, however, there was reflux of the contrast towards the brain, demarcating the lateral ventricles. In the transcranial ultrasound examination, the right and left lateral cerebral ventricles were dilated with homogeneous anechoic liquid content, confirming the diagnosis of congenital internal hydrocephalus. As the pig showed neurological changes, absence of the sucking reflex and inability to stand up, making its maintenance unfeasible and reducing the possibility of survival, the animal was euthanized. The male pig was referred for necropsy, where had cranial vault bones enlarged and thin, cerebral hemispheres that collapsed when removed from the skull, accentuated dilation of the lateral ventricles and atrofia of the cortical white matter. The histological exam revealed atrophy of the white matter and reduced number of the gray matter glial cells, associated to marked dilation of the lateral ventricles. The mesencephalic aqueduct was covered by a layer of ependymal cells that were abruptly discontinuous, forming several ependymal canalicules (stenosis). The final diagnosis was severe internal hydrocephalus. The diagnosis of congenital internal hydrocephalus was based on clinical findings, imaging exams, necropsy and histopathological findings. Discussion: In the pig studied, clinical signs of congenital hydrocephalus occurred in the 1st days of life. The specific cause of hydrocephalus in the case report, was the stenotic mesencephalic aqueduct that gave rise to illness were seen in microscopic examination. In the case reported, ultrasound examinations, in persistent fontanelles, and plain and contrast x-rays were performed, the findings of radiographs were consistent for the diagnosis of hydrocephalus. On ultrasound, enlarged lateral ventricles filled with anechoic fluid were observed, corroborating findings by literature. The necropsy macro and microscopic findings, corroborate with findings of other species with congenital hydrocephalus. More studies regarding clinical signs and parameters of complementary exams, such as ultrasound and radiography, are necessary to characterize and detail hydrocephalus in pigs. Keywords: neurology, cerebrospinal fluid, ultrasound, myelography.